Thoracic ultrasound competence for ultrasound-guided pleural procedures. (23rd December 2019) - McCracken, David J.; Laursen, Christian B.; Barker, Graham; Gleeson, Fergus V.; Cullen, Kathy M.; Rahman, Najib M.
Focused thoracic ultrasound has become essential in the guidance and direction of pleural interventions to reduce unwanted complications and as a result now forms a crucial component of physician training. Current training standards along with assessment methods vary widely, and are often not robust enough to ensure adequate competence. This review assesses the current state of training and assessment of thoracic ultrasound competence in various settings, allowing comparison with alternative competency based programmes. Future directions for training and assessment of thoracic ultrasound competence are discussed. Focused thoracic ultrasound is essential in the guidance of pleural interventions to reduce unwanted complications. It forms a crucial component of physician training. Current training standards and assessment methods vary. http://bit.ly/2me8hoU